2007
DOI: 10.1007/s10683-006-9140-2
|View full text |Cite
|
Sign up to set email alerts
|

Can intertemporal choice experiments elicit time preferences for consumption?

Abstract: The paper considers what can be inferred about experimental subjects’ time preferences for consumption from responses to laboratory tasks involving tradeoffs between sums of money at different dates, if subjects can reschedule consumption spending relative to income in external capital markets. It distinguishes three approaches identifiable in the literature: the straightforward view; the separation view; and the censored data view. It shows that none of these is fully satisfactory and discusses the resulting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
67
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(72 citation statements)
references
References 17 publications
0
67
1
Order By: Relevance
“…We may have found less decreasing impatience for money due to market forces. As money is tradable on financial markets and transferable across time, people's discounting of money may have been disciplined by the prevailing interest rates for money (Cubitt and Read 2007). However, we also found that time preferences were less stable for money than for health, which seems to contradict the above conjecture.…”
Section: Discussioncontrasting
confidence: 65%
“…We may have found less decreasing impatience for money due to market forces. As money is tradable on financial markets and transferable across time, people's discounting of money may have been disciplined by the prevailing interest rates for money (Cubitt and Read 2007). However, we also found that time preferences were less stable for money than for health, which seems to contradict the above conjecture.…”
Section: Discussioncontrasting
confidence: 65%
“…A solution could be to offer experimental interest rates that lie between the subjects' "real-world" borrowing and lending rates (as done by Coller and Williams, 1999). Even in this case, however, Cubitt and Read (2007) demonstrate that choices in the experiment do not necessarily reveal the subjects' time preferences.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we avoid problems that arise for some intertemporal decision experiments if capital markets and/or storage allow consumption to be rescheduled across time relative to income when the analysis assumes consumption and income to be simultaneous (for discussion, see, e.g., Cubitt andRead 2007, Frederick et al 2002).…”
mentioning
confidence: 99%